A SOA web-based group decision support system considering affective aspects - Conceição, Luís (2017)
The topic of Group Decision Support Systems (GDSS) has been studied over the last decades. Supporting decision-makers that participate in group decision-making processes is a complex task, especially when decision-makers have no opportunity to gather at the same place and at the same time. In this work, we propose a Web based Group Decision Support System (WebGDSS) which intends to support decision-makers anywhere, anytime and through almost any kind of devices. Our system was developed under a SOA architecture and we used a multi criteria algorithm that features decision-makers’ cognitive aspects, as well as a component of generation of intelligent reports to feedback the results of decision-making processes to the decision-makers.